Utilization of Microfiber Waste as Material to Add Paving Block Based on Compressive Strength and Absorption Testing - Feny Ratna Fadlila; Fiki Rika Amalia; Riza Susanti; Puji Widodo (Journal of Education Technology Information Social Sciences and Health, 2022)
Along with the implementation of infrastructure development, the need for building materials in Indonesia will continue to increase. Building materials themselves are generally sourced from Indonesia's natural resources (SDA). But lately people have an interest in the use of environmentally friendly products. Seeing these two things gave rise to new thoughts to replace some of the aggregates in paving blocks using microfiber waste where microfiber waste is synthesis waste that is difficult to recycle. Experimental studies were chosen as a method in this study which was carried out directly and objectively. This study used a percentage of 0%; 0,25%; 0,5%; 0.75%, and 1% which results in a compressive strength value of 34.03 Mpa; 25.72 Mpa; 34.12 Mpa; 29.29 Mpa; and 23.66 Mpa. The optimum value of the compressive strength of the paving block was obtained at a percentage of 0.5% which is 34.11 Mpa. As well as producing a water absorption value of 4.42%, each of which produces a value of 4.42%; 4,34%: 5,09%; 4.78% which is included in the B quality category while the 1% percentage of 6.7% is included in the C quality category.